2020
DOI: 10.1007/s12664-020-01047-6
|View full text |Cite
|
Sign up to set email alerts
|

An Indian national survey of therapeutic drug monitoring with anti-tumor necrosis (TNF) medications in inflammatory bowel disease

Abstract: Background Evidence supports therapeutic drug monitoring (TDM) in improving efficacy and cost-effectiveness of anti-TNF therapy in inflammatory bowel disease (IBD). Data on perceptions and barriers to TDM use are limited and no data are available from India. Our objective was to assess clinicians' attitudes and barriers to TDM use in IBD. Methods A 16-question survey was distributed to members of the Indian Society of Gastroenterology. Information on clinician characteristics, demographics, use and barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Klara et al reported that in their patient's trough levels of immunosuppressants after liver transplantation and kidney transplantation were often found to be outside the target range 39 . A recent study published by Patel et al reported that amongst 101 Indian Gastroenterologists who responded to their survey, 20% of them used TDM proactively for anti‐TNF therapy in inflammatory bowel disease 40 . TDM of immunosuppressants is extensively performed in Indian clinical practice, especially for post‐transplant patients, and many Indian studies have been published about the same 41,42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Klara et al reported that in their patient's trough levels of immunosuppressants after liver transplantation and kidney transplantation were often found to be outside the target range 39 . A recent study published by Patel et al reported that amongst 101 Indian Gastroenterologists who responded to their survey, 20% of them used TDM proactively for anti‐TNF therapy in inflammatory bowel disease 40 . TDM of immunosuppressants is extensively performed in Indian clinical practice, especially for post‐transplant patients, and many Indian studies have been published about the same 41,42 …”
Section: Resultsmentioning
confidence: 99%
“…39 A recent study published by Patel et al reported that amongst 101 Indian Gastroenterologists who responded to their survey, 20% of them used TDM proactively for anti-TNF therapy in inflammatory bowel disease. 40 TDM of immunosuppressants is extensively performed in Indian clinical practice, especially for post-transplant patients, and many Indian studies have been published about the same. 41,42…”
Section: Sion Consisting Of Calcineurin Inhibitors (Cni) (Tacrolimus [Tac]mentioning
confidence: 99%
“…Both reactive and proactive TDM are being used more frequently in everyday clinical practice as a tool to better optimize anti-TNF therapy in IBD and achieve favorable therapeutic outcomes [ 10 , 11 , 12 ]. Several assays are now available for measuring drug concentrations and antidrug antibodies to anti-TNF therapies [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TNF therapies have transformed the care of inflammatory bowel disease, but these are immunogenic and associated with the loss of response [8]. Despite an increasing therapeutic armamentarium, it is advisable to optimize therapy within class when possible [9]. Marutani and colleagues report from Nagoya Memorial Hospital, Nagoya, Japan a retrospective experience of effectiveness of a second anti-TNF therapy after "failure" of first anti-TNF agent in patients with ulcerative colitis (UC) [10].…”
Section: Efficacies Of First and Second Tumor Necrosis Factor Inhibitmentioning
confidence: 99%